2020
DOI: 10.1038/s41598-019-56589-3
|View full text |Cite|
|
Sign up to set email alerts
|

Deep learning, computer-aided radiography reading for tuberculosis: a diagnostic accuracy study from a tertiary hospital in India

Abstract: In general, chest radiographs (CXR) have high sensitivity and moderate specificity for active pulmonary tuberculosis (ptB) screening when interpreted by human readers. However, they are challenging to scale due to hardware costs and the dearth of professionals available to interpret cXR in low-resource, high ptB burden settings. Recently, several computer-aided detection (cAD) programs have been developed to facilitate automated cXR interpretation. We conducted a retrospective case-control study to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 14 publications
0
55
0
Order By: Relevance
“… 27 A retrospective case–control study was conducted in a tertiary hospital from India using microbiologically-confirmed TB as the reference standard, which reported that qXR (v2) could detect TB with an AUC of 0.81, a sensitivity of 71% and a specificity of 80%. 28 As many patients who present at tertiary hospitals have symptoms suggestive of TB, accurate and rapid triage tests that can rule out the disease are needed. Thus, the CAD software as a triage test for TB might be more suitable for the primary care level in settings where access to radiologists is limited than the tertiary care level.…”
Section: Cad With DL Technology In Tb Detectionmentioning
confidence: 99%
“… 27 A retrospective case–control study was conducted in a tertiary hospital from India using microbiologically-confirmed TB as the reference standard, which reported that qXR (v2) could detect TB with an AUC of 0.81, a sensitivity of 71% and a specificity of 80%. 28 As many patients who present at tertiary hospitals have symptoms suggestive of TB, accurate and rapid triage tests that can rule out the disease are needed. Thus, the CAD software as a triage test for TB might be more suitable for the primary care level in settings where access to radiologists is limited than the tertiary care level.…”
Section: Cad With DL Technology In Tb Detectionmentioning
confidence: 99%
“…25 Several studies have compared the accuracy of AI and radio logists; however, the number of radiologists included in these studies was often less than ten. 14,26,27 Here we evaluate a deep-learning model designed to assist clinicians in the interpretation of chest x-rays, encompassing the full range of clinically relevant findings on frontal and lateral chest x-rays.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research shows that AI algorithms can even achieve or exceed the performance of human experts in certain medical image diagnosis tasks, including lung diseases [11][12][13][14][15][16][17] . Comparing to other lung diseases, such as lung nodule detection [18][19][20] , tuberculosis diagnosis 16,21 , and lung cancer screening 15 , differentiating COVID-19 from other pneumonias has unique difficulty, i.e., high similarity of pneumonias of different types (especially in early stage) and large variations in different stages of the same type. Hence, developing AI diagnosis algorithm specific to COVID-19 is necessary.…”
mentioning
confidence: 99%